PENTINGNYA GURU PROFESSIONAL DALAM MENDIDIK SISWA MILENIAL UNTUK MENGHADAPI REVOLUSI 4.0 - Indah Wati; Insana Kamila (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Competencies that must be owned by a teacher in educating students must link and match to the development of globalization industry. This is related to learning methods, attitudes, and material that will be delivered to the students. Nowadays, we are in the era of globalization or the 21st century with the development of industry known as revolution 4.0. New trends that are emerging related to technology used to support teaching and learning process in the classroom are very rapid and growing. This is directly in line with the development of students in this era. The generation which is currently called the millennial generation is a person who is critical and sophisticated in using technology. As a professional teacher, we must be able to keep up with the times and adjust the way to teach and bring material well so that it is easily understood by students.